Echo-Doppler evaluation of diastolic filling in differently induced left ventricular hypertrophy - Giunta, A; Maione, S; Biagini, R; del Rosso, P; Sifola, C; Tuccillo, B (Cor et vasa, 1989)
The study was performed in order to assess whether left ventricular hypertrophy (LVH) (exercise or pressure-overload induced but of a similar extent) may differently affect LV diastolic function. The authors compared LV filling echo-Doppler indexes of 16 male trained rowers (mean left ventricular mass index (LVMI) = 162 +/- 18 g/m2) with those of 34 male patients with secondary LVH, subdivided into two groups according to the extent of LVH (group I, n = 20, with a mean LVMI = 159 + 20 g/m2, and group II, n = 14, with a mean LVMI = 221 +/- 23 g/m2). No abnormalities of LV diastolic filling were observed in the athletes; while in patients with secondary LVH of group I an impairment of the echo-Doppler indexes was detected. A more severe involvement of the diastolic properties was observed in patients with LVH of group II.
Keywords: Echocardiography, Doppler; srdeční komory; Male; hypertenze; Cardiac Volume; srdeční selhání; Adolescent; objem srdce; Adult; diastola; dospělí; mužské pohlaví; Aortic Valve Stenosis; aortální stenóza; Hypertension; rychlost toku krve; mladiství; Cardiomegaly; Myocardial Contraction; dopplerovská echokardiografie; lidé; kardiomegalie; Heart Failure; Humans; Diastole; kontrakce myokardu; Systole; systola; Heart Ventricles; Blood Flow Velocity